2005
DOI: 10.1152/ajpendo.00113.2004
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of β2-adrenergic receptors in mouse liver alters the expression of gluconeogenic and glycolytic enzymes

Abstract: .-In the livers of humans and many other mammalian species, ␤ 2-adrenergic receptors (␤2-ARs) play an important role in the modulation of glucose production by glycogenolysis and gluconeogenesis. In male mice and rats, however, the expression and physiological role of hepatic ␤ 2-ARs are rapidly lost with development under normal physiological conditions. We previously described a line of transgenic mice, F28 (André C, Erraji L, Gaston J, Grimber G, Briand P, and Guillet JG. Eur J Biochem 241: [417][418][419][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
(51 reference statements)
2
25
1
Order By: Relevance
“…Epinephrine secreted from the adrenal medulla prepares the body to meet an emergency. Circulating glucagon and epinephrine activate cellular signals that catalyze components of adenylate cyclase via the stimulatory guanine nucleotide binding regulatory protein Gαs (Jelinek et al, 1993, Erraji-Benchekroun et al, 2005. This signal increases formation of cAMP and other transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Epinephrine secreted from the adrenal medulla prepares the body to meet an emergency. Circulating glucagon and epinephrine activate cellular signals that catalyze components of adenylate cyclase via the stimulatory guanine nucleotide binding regulatory protein Gαs (Jelinek et al, 1993, Erraji-Benchekroun et al, 2005. This signal increases formation of cAMP and other transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…1b, neg ctrl panel) and staining of liver tissue (Fig. 1b, liver panel) reported to be negative for both ␤1-AR and ␤2-AR (27,28). mRNA expression of ␤1-AR (Adrb1) and ␤2-AR (Adrb2) in DCT2/CNT cells isolated from pTRPV5-EGFP mice using the COPAS Biosorter, was determined by real-time PCR.…”
Section: Resultsmentioning
confidence: 99%
“…27) Loubna et al also found increased ADRB 2 expression in the liver of F28 mice could protect liver cells from apoptosis and lower the body mass index, mainly due to the ADRB 2 linked increase of hepatic cAMP activity. 28) Unexpectedly, there were some differences of hepatic Gsα-cAMP signal axis in high IR stage in HSHF-diet rats. The hepatic Gsα-cAMP signal axis was desensitized and almost reduced to that of normal chow-diet rats, in the face of chronic HSHF-diet stimulation.…”
Section: Camp Concentration In Livermentioning
confidence: 93%